Faktor Faktor Yang Mempengaruhi kualitas laporan keuangan Dan Dampaknya Terhadap Minat Membayar Zakat - Yuhanis Ladewi; Mizan Mizan; Indah Rizki Gustiriyani (ITB AAS INDONESIA Surakarta, 2023)
This study aims to determine partially the effect of transparency and accountability on the quality of financial reports and their impact on intention to pay zakat. The type of research used is descriptive and associative research. The variables used transparency, accountability, quality of financial reports, and intention to pay zakat. The location of the research was carried out at the National Amil Zakat Agency, South Sumatra Province. The population used is 104 respondents. The sample used is saturated sample. The data used are primary and secondary data, as well as data testing using validity and reliability tests. The analysis technique used is descriptive statistics and inferential statistics (normality test, multicollinearity test and heteroscedasticity test) and the coefficient of determination test (R²) as well as path analysis and hypothesis testing (t). Research data processing was assisted by the SPSS version 25 computer program. The results of the study can be concluded partially (t test) showing that partially accountability affects the quality of financial reports. While transparency has no significant effect on the quality of financial reports. Accountability and quality of financial statements have a significant effect on the intention to pay zakat. Meanwhile, transparency has no significant effect on the intention to pay zakat